Herbario Virtual. Levantamiento de la Base de Datos - Jácome Vásquez, Ángel Patricio (2018)
This research project is based on the use of technology to carry out the collection of the herbarium database, from the Technical University of Cotopaxi, which will be available on the institution's website, thus allowing free access to people interested in visiting it and acquiring knowledge of the different botanical species collected in the province with their respective location, classification, common and scientific name, description, usefulness, among other parameters contemplated for the presentation of the species.